2022
DOI: 10.1021/acs.jpclett.2c01482
|View full text |Cite
|
Sign up to set email alerts
|

Internal Electric Field-Induced Formation of Exotic Linear Acetonitrile Chains

Abstract: The application of external electric and magnetic fields is a powerful tool for aligning molecules in a controlled way, if the thermal fluctuations are small. Here we demonstrate that the same holds for internal electric fields in a molecular cluster. The electric field of a single molecular dipole, HCl, is used to manipulate the aggregation mechanism of subsequently added acetonitrile molecules. As a result, we could form exotic linear acetonitrile (CH3CN) chains at 0.37 K, as confirmed by infrared spectrosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…49 explored the positive and negative cooperativity effects in ternary complexes formed by two imidazole and F 2 TO (T = C, Si, and Ge) molecules. In a high-resolution infrared spectroscopic study, Mani et al 60 Given the importance of the hydrogen-bonding and carbonbonding interactions, a comprehensive understanding of the trends of cooperativity between these two interactions is needed. This prompted us to undertake the current study, in which we have chosen 42 trimeric complexes to study this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…49 explored the positive and negative cooperativity effects in ternary complexes formed by two imidazole and F 2 TO (T = C, Si, and Ge) molecules. In a high-resolution infrared spectroscopic study, Mani et al 60 Given the importance of the hydrogen-bonding and carbonbonding interactions, a comprehensive understanding of the trends of cooperativity between these two interactions is needed. This prompted us to undertake the current study, in which we have chosen 42 trimeric complexes to study this phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…explored the positive and negative cooperativity effects in ternary complexes formed by two imidazole and F 2 TO (T = C, Si, and Ge) molecules. In a high-resolution infrared spectroscopic study, Mani et al found a positive cooperativity between carbon and hydrogen bond in CH 3 CN···CH 3 CN···HCl and HCl···CH 3 CN···HCl trimers, which was reflected in the observed redshifts in the stretching frequencies of the hydrogen-bonded HCl in the trimers as compared to that in the hydrogen-bonded CH 3 CN···HCl dimer.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations